Antimicrobial use on 74 Japanese pig farms in 2019: A comparison of Japanese and European defined daily doses in the field. - Kyoko Fujimoto (Public Library of Science (PLoS), 2021)
Defined daily doses (DDD) have been established in human medicine to standardize the measurement of treatment in a population. In veterinary medicine, the European Medicine Agency published defined daily dose (DDDvet) values for antimicrobial agents used in food-producing animals in 2016. National defined doses (DDDjp) for antimicrobials used for pigs in Japan have recently been determined. The aim of this study was to compare the results of calculated antimicrobial use in the field using the DDDjp and DDDvet values. Data from 74 pig farms in Japan relative to antimicrobial use in 2019 was collected. The numbers of DDDs (the weight of biomass treated in kg-days) using DDDjp and DDDvet values for each farm and for different antimicrobial classes were compared. Associations between calculated numbers of DDDjp and DDDvet on farm level were investigated. In addition, differences in antimicrobial use were investigated between different production types of farms (farrowing, finishing and farrow-to-finish farms). Using DDDjp and DDDvet values, the aggregated number of DDDs for 74 farms were 4,099,188 and 2,217,085 respectively, with the former being larger by 1.85 times than the latter. The most frequently used antimicrobial class was penicillin regardless of whether DDDjp or DDDvet was used. The absence of DDDvet values for certain antimicrobial agents used in Japan and the differences in the number of DDDjps/PCU and DDDvets/PCU indicated the need for Japanese DDDs. The number of DDDs per kg population correction unit (PCU) per farm tended to be higher in farrowing farms than in farrow-to-finish farms and finishing farms, with no significant difference (P = 0.19).